Labour-saving rice harvester - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
As more and more people are leaving the rural areas to search for employment in the urban centres, the problem of finding enough people to work at labour-intensive times, such as harvesting, is increasing. Realizing that this was the case with rice...